PENTINGNYA PENGUASAAN APLIKASI MICROSOFT OFFICE UNTUK MENINGKATKAN KEMAMPUAN HARD SKILL MAHASISWA - Anisa, Desfa; Kusumo, Retno; Natasha (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
The development of technology at this time has progressed very rapidly, especially in application software on computers. One application program that is currently developing along with information and communication technology is Microsoft office which can be used to perform document processing and administration. Microsoft Office is deemed necessary to be taught to students regarding the use of these applications, especially Microsoft Excel applications in order to improve students' abilities in using formulas in Microsoft Excel. Microsoft Excel is part of Microsoft Office which is often used for processing numbers. The method used is the tutorial method (assistance), question and answer and direct practice using the application. The material presented consists of an introduction to functions and formulas in Microsoft Excel. There were 12 participants who took part in this activity. This activity begins with the delivery of material in the form of a presentation (tutorial) and the material presented is immediately practiced by students.